Halal Tourism Development in Lombok, Indonesia: A SWOT Analysis - Akbar Dimas Satria; Syauqi Imam Ahmadi; Habibillah Hakiki (Halal Tourism and Pilgrimage, 2022)
This study aims to analyze the implementation of Thailand's halal tourism strategy on Lombok Island Indonesia, and provide suggestions for improving the halal tourism industry in Lombok. Based on the research results, there are several strategies that can be implemented in Lombok, including improving the quality of halal tourism products and services, promoting halal tourism, and developing infrastructure that supports halal tourism. Therefore, collaboration between local governments, tourism industry players, and the local community is needed to implement an effective and consistent halal tourism strategy in Lombok.